2016
DOI: 10.1186/s12877-016-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring moderate-intensity walking in older adults using the ActiGraph accelerometer

Abstract: BackgroundAccelerometry is the method of choice for objectively assessing physical activity in older adults. Many studies have used an accelerometer count cut point corresponding to 3 metabolic equivalents (METs) derived in young adults during treadmill walking and running with a resting metabolic rate (RMR) assumed at 3.5 mL · kg−1 · min−1 (corresponding to 1 MET). RMR is lower in older adults; therefore, their 3 MET level occurs at a lower absolute energy expenditure making the cut point derived from young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 46 publications
4
79
2
Order By: Relevance
“…Similarly, Barnett et al . determined an age‐specific LPA–MVPA transition threshold in a population of older adults (mean age 70.2), in a calibration study against indirect calorimetry . The use of these age‐specific thresholds in our study partially overcomes the previously described shortcomings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Barnett et al . determined an age‐specific LPA–MVPA transition threshold in a population of older adults (mean age 70.2), in a calibration study against indirect calorimetry . The use of these age‐specific thresholds in our study partially overcomes the previously described shortcomings.…”
Section: Discussionmentioning
confidence: 91%
“…10 Similarly, Barnett et al determined an age-specific LPA-MVPA transition threshold in a population of older adults (mean age 70.2), in a calibration study against indirect calorimetry. 20 The use of these age-specific thresholds in our study partially overcomes the previously described shortcomings. Nevertheless, and very importantly, we acknowledge that there could still be bias because of variability in several factors that might influence energy cost, such as sex, fitness, body weight, disability, movement impairment, and illnesses.…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…A walking speed of 2.5 km/h was considered consistent with MVPA for an older population , particularly one with elevated pain (mean Knee Injury and Osteoarthritis Outcome Score [KOOS] pain = 50) and limited function due to OA. We used an estimated stride length of 0.6 m (derived from a measured step length of 0.3 m) to conclude that at least 67 strides/min would be needed to achieve a speed of 2.5 km/h.…”
Section: Methodsmentioning
confidence: 99%
“…Triaxial, medical‐grade accelerometers like the ActiGraph GT3X+ (ActiGraph Corporation) are considered the gold standard for PA evaluation , yet guidelines for interpreting accelerometry data are not standardized in the literature . Studies have proposed multiple threshold cutoffs to relate ActiGraph counts to PA levels, and some have suggested that thresholds should be described as ranges to account for interperson variability . Furthermore, much accelerometry validation has involved young and healthy populations or uniaxial ActiGraphs , the results of which are not applicable to the older OA population using triaxial accelerometers .…”
Section: Introductionmentioning
confidence: 99%
“…Waistworn accelerometer data are used to derive average minutes/day of light, moderate and vigorous physical activity, while the inclinometer is used to assess sedentary behaviour using established protocols. 89 90 We quantify complexity of trip routes (i.e., the cognitive difficulty of Open access navigational activities) in terms of length, street intersections crossed and number of turns at intersections using GIS software. Wrist-worn accelerometer data are used to quantify total sleep time and efficiency, waking after sleep onset and number of long wake episodes.…”
Section: Measures Of Cognitive Functionmentioning
confidence: 99%